Classical immunomodulatory therapy in multiple sclerosis: how it acts, how it works - Amélia Mendes; Maria José Sá (Arquivos de Neuro-Psiquiatria)
Interferon beta (IFNβ) and glatiramer acetate (GA) were the first immunomodulators approved to the treatment of relapsing-remitting multiple sclerosis (MS) and clinically isolated syndromes. Despite the enlargement of the therapeutic armamentarium, IFNβ and GA remain the most widely drugs and the therapeutic mainstay of MS. OBJECTIVE: To review the mechanisms of action of IFNβ and GA and main clinical results in MS. RESULTS: IFNβ modulates T and B-cell activity and has effects on the blood-brain barrier. The well proved mechanism of GA is an immune deviation by inducing expression of anti-inflammatory cytokines. Some authors favor the neuroprotective role of both molecules. Clinical trials showed a 30% reduction on the annualized relapse rate and of T2 lesions on magnetic resonance. CONCLUSION: Although the precise mechanisms how IFNβ and GA achieve their therapeutics effects remain unclear, these drugs have recognized beneficial effects and possess good safety and tolerability profiles. The large clinical experience in treating MS patients with these drugs along almost two decades deserves to be emphasized, at a time where the appearance of drugs with more selective mechanisms of action, but potentially less safer, pave the way to a better selection of the most appropriate individualized treatment.